Emperors and ancestors : Roman rulers and the constraints of tradition - Hekster, Olivier (Oxford studies in ancient culture and representation, 2015)
This is the first systematic analysis of the different ways in which Roman imperial lineage was represented in the various 'media' through which images of emperors could be transmitted. Rather than focusing on individual rulers of the Roman Empire, it evaluates evidence over an extended period of time and differentiates between various types of sources, such as inscriptions, sculpture, architecture, literary text, and particularly central coinage, which forms the most convenient source material for a modern reconstruction of Roman representations of power over a prolonged period of time